KOMISJA EDUKACJI NARODOWEJ A ENCYKLOPEDIA, ALBO SŁOWNIK ROZUMOWANY NAUK, SZTUK I RZEMIOSŁ (CZ. 1. WYMIAR WYCHOWAWCZY) - Janeczek, Stanisław (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
This paper combines on the one hand the educational ideals and didactics in the schools of the Polish–Lithuanian Commonwealth reformed by the Commission of National Education (1773), and on the other hand one of the most representative testimonies of the then intellectual culture, i.e. Encyclopédie ou dictionnaire universel raisonné des sciences, des arts et des métiers, published in the years 1751–1780. The activity of the Commission, likewise its preceding reforms carried out in the Commonwealth in church schooling in the mid-eighteenth century, correspond with analogous changes in Europe, their specific example manifestation Encyclopédie. Their spirit was similar, it sought to reconcile modern utilitarianism – appropriate to the needs of absolutist states, which had taken the concern for education from religious groups – with an integral vision of school. In this vision, the fundamental elements was moral formation combined with religious formation. Despite some manifestations of certain rationalism and naturalism, in line with the spirit of the epoch, rather more typical of Encyclopédie than the Commission’s schooling, religion remained the foundation of morality, and the latter was the ground of the social order.